Evaluation of wheat middlings as a supplement for cattle consuming winter range forage - G.D. Sunvold; R.C. Cochran; E.S. Vanzant; S.D. Brandyberry; R.B. Hightshoe; T. DelCurto (Kansas Agricultural Experiment Station Research Reports, 1989)
Intake of dormant, bluestem-range forage was increased by feeding steers supplements based on wheat middlings or soybean meal + sorghum grain, although the degree of influence on forage intake depended on type and level of supplementation. All supplements increased (P<.10) total diet digestibility. However, fiber digestibility tended to be slightly lower for steers receiving the high level of wheat middlings and the soybean meal + sorghum grain supplement.
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Wheat middlings; Winter range forage